Effication of Convalence Plasma Therapy in Covid-19 Patients: Systemic Review and Meta – Analysis - Diyono, Diyono; Sriwiyati, Lilik (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Introduction: COVID-19 has developed into a global pandemic and until now no definitive therapy has been found. COVID-19 mortality is relatively high, especially in patients who have comorbidities. Convalescent plasma therapy, which has been widely used, has not been universally recognized as being able to improve the recovery of COVID-19 patients. Objective: This study aims to determine the efficacy of convalescent plasma therapy in COVID-19 patients. Methods: The research design is a systematic review and meta analysis. Data were obtained from the electronic journal database PubMed, Cochrane Library, ProQuest, SpringerLink, ScienceDirect, Scopus, and Google Scholar with Medical Subject Heading (Mesh)